Early Initiation of Antenatal Care and Factors Associated with Early Antenatal Care Initiation at Health Facilities in Southern Ethiopia - Mengesha Boko Geta; Walelegn Worku Yallew (Hindawi Limited, 2017)
Antenatal care (ANC) is care given to pregnant mothers to timely identify and mitigate pregnancy related problems that can harm mother or fetus. Most of Ethiopian mothers present late for ANC. The aim of this paper was to assess determinants of early antenatal care initiation among pregnant women. Mothers attending Shebedino District Health Centers for ANC between January 12 and February 18, 2015, were invited to the study. Multistage sampling technique and structured questionnaire were used to collect data by trained data collectors. Univariate and bivariate analysis were conducted to study the association between explanatory and outcome variable. Out of 608 women, 132 [21.71%] had their first ANC within the recommended time [before or at 3 months]. Media access [AOR = 2.11 95% CI 1.00, 3.22], knowledge about the correct time of ANC booking [AOR = 4.49 95% CI 2.47, 6.16], and having been advised to book within 12 weeks [AOR = 4.14 95% CI 3.80, 5.21] were determinants of first-trimester booking. Health professionals and care providers should provide full information, advice, and appropriate care about early ANC for every eligible mother.